Weed suppression and antioxidant activity of Astragalus sinicus L. decomposition leachates - Liu, Silin; Wang, Wenhui; Chen, Jiaoyun; Ma, Zhiyu; Xiao, Youping; Chen, Zhongwen; Zhang, Ying; Du, Xiao; Mu, Yinghui (Frontiers in Plant Science, 2022)
Astragalus sinicus L. (milk vetch), a versatile plant that has a soil-enriching effect as green manure, is widely planted in the temperate zone of China. In previous experiments, milk vetch incorporated into the soil as green manure showed potential for weed control. But, ‘what was exactly happening at the chemical level?’ and ‘which were the compounds potentially responsible for the phytotoxic effects observed during those previous assays?’ In a recent study, in-vitro phytotoxicity bioassays and chemical analyses of milk vetch decomposition leachates were carried out to explore the relationship between the temporal phytotoxic effects and the dynamics of chemical composition. For that, milk vetch decomposition leachates with a decay time of 12 h, 9 d, 12 d, 15 d, and 18 d were analyzed for organic compounds by liquid chromatography (LC). The main results are as follows: (1) three compounds with weed suppression potential produced during the decomposed process, i.e., 4-ethylphenol, N-acrylimorpholine and allyl isothiocyanate. 2-hydroxyethyl acrylate was present in the 12 h decomposition leachates but was at its highest concentration of 127.1 µg mL-1 at 15 d. (2) The cultures were configured according to the four concentrations of weed-resistant active substances measured in the 15 d decomposition leachate and, as with the 15 d decomposition leachate, the mixture cultures inhibited 100% of goosegrass germination at the high concentrations (≥ 30%), which suggests that these substances have weed suppression potential. (3) The high total phenol content (302.8 - 532.3 mg L-1), total flavonoid content (8.4 - 72.1 mg L-1), and the reducing activity of the decomposition leachates for different decay times may explain why the incorporation of milk vetch into the soil did not lead to peroxidation of goosegrass in the previous study. (4) Finally, the changes in acid fraction and total content (1.9 - 4.2 mg mL-1) for different decay times explain the variations in pH of the decomposing leachates, which, when discussed in conjunction with previous studies, may lead to changes in soil nutrient effectiveness and consequently affect crop growth. This study provided a reference for green weed control research.